2015
DOI: 10.5194/bgd-12-17329-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ammonium excretion and oxygen respiration of tropical copepods and euphausiids exposed to oxygen minimum zone conditions

Abstract: Abstract. Calanoid copepods and euphausiids are key components of marine zooplankton communities worldwide. Most euphausiids and several copepod species perform diel vertical migrations (DVMs) that contribute to the export of particulate and dissolved matter to midwater depths. In vast areas of the global ocean, and in particular in the eastern tropical Atlantic and Pacific, the daytime distribution depth of many migrating organisms corresponds to the core of the oxygen minimum zone (OMZ). At depth, the animal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
2
3
1
Order By: Relevance
“…While the total abundance of krill is probably underestimated by the comparatively slow and small plankton net, their vertical distribution in relation to the OMZ and the marked total decrease within the eddy compared to outside stations suggests that they are susceptible to OMZ conditions and may suffer from increased predation in the surface layer. This is in line with physiological observations, where a critical partial pressure of 2.4 and 6.2 kPa (29.6 and 64.2 µmol O 2 kg −1 ) was determined at subsurface (13 • C) and near-surface temperatures (23 • C), respectively, in Euphausia gibboides in the ETNA (Kiko et al, 2015). Calanoid copepods represent the largest group in terms of abundance and biomass and comprise approximately 100 species in Cabo Verdean waters (Séguin, 2010) with a wide range of physiological and behavioural adaptations.…”
Section: Shallow Omz Avoidance and Compression At The Surfacesupporting
confidence: 91%
See 1 more Smart Citation
“…While the total abundance of krill is probably underestimated by the comparatively slow and small plankton net, their vertical distribution in relation to the OMZ and the marked total decrease within the eddy compared to outside stations suggests that they are susceptible to OMZ conditions and may suffer from increased predation in the surface layer. This is in line with physiological observations, where a critical partial pressure of 2.4 and 6.2 kPa (29.6 and 64.2 µmol O 2 kg −1 ) was determined at subsurface (13 • C) and near-surface temperatures (23 • C), respectively, in Euphausia gibboides in the ETNA (Kiko et al, 2015). Calanoid copepods represent the largest group in terms of abundance and biomass and comprise approximately 100 species in Cabo Verdean waters (Séguin, 2010) with a wide range of physiological and behavioural adaptations.…”
Section: Shallow Omz Avoidance and Compression At The Surfacesupporting
confidence: 91%
“…Many zooplankton and nekton taxa perform diurnal vertical migrations (DVMs), usually spending the daylight hours in the mesopelagic OMZ and migrating into the productive surface layer at night. These taxa include for example euphausiids (Tremblay et al, 2011), sergestid and penaeid shrimp (Andersen et al, 1997), myctophid fishes (Kinzer and Schulz, 1985) as well as several large calanoid copepods (e.g. Pleuromamma species, Teuber et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference between control and treatment decreased with incubation, revealing that copepods were excreting this compound. Our estimated rates are close to those reported in this zone in winter (P erez-Arag on et al 2011), but lower than those reported for other upwelling zones (Isla et al 2004;Fern andez-Urruzola et al 2016;Kiko et al 2015). In the second experiment, NH 1 4 decreased with incubation for both treatments and controls, which could be due to the high degree of lability of NH 1 4 in natural environments since it is actively used by phytoplankton and microbial communities.…”
Section: Nitrogen Excretion By Copepodssupporting
confidence: 82%
“…In the same study, NH + 4 production was not detected in spring, in contrast with our study, in which NH + 4 was the main compound excreted by copepods. Additionally, the NH + 4 excretion rates observed in the current study were higher than those reported in this area and were also in the range of those reported in other upwelling zones (Fernández-Urruzola et al, 2016;Kiko et al, 2016).…”
Section: Excretion Of Nitrogen and Phosphorus Compoundscontrasting
confidence: 52%